Senior Management of the Russian Union of Pediatricians - Valery Yu. Albitsky (Вопросы современной педиатрии)
The article tells about the chairmen of the Russian Union of Pediatricians — Members of the USSR Academy of Medical Sciences, Honored Workers of Science, senior management of the professional community of pediatricians during the period of over 90 years since the establishment to the present time. The publication presents the results of studying the biographies and scientific works of the luminaries of Russian pediatrics such as A. A. Kisel and G. N. Speranskiy, who linked the Tsarist and Soviet medicine. The basic milestones of professional activities of the great Soviet pediatricians Y. F. Dombrovskaya and A. F. Tur are shown. The biographies of the World War II veterans V. P. Bisyarina, M. Y. Studenikin and A. V. Mazurin, decent representatives of Russian pediatrics at the end of the Soviet era, are described. The outstanding contribution of the Academician of the Russian Academy of Science A. A. Baranov, who initiated the creation of the Russian Union of Pediatricians as the legal successor of the All-Union and All-Russian Society of Pediatricians, is emphasized.